2008
DOI: 10.1017/s030500090700829x
|View full text |Cite
|
Sign up to set email alerts
|

Infant gaze following and pointing predict accelerated vocabulary growth through two years of age: a longitudinal, growth curve modeling study

Abstract: We found that infant gaze following and pointing predicts subsequent language development. At ages 0 ; 10 or 0 ; 11, infants saw an adult turn to look at an object in an experimental setting. Productive vocabulary was assessed longitudinally through two years of age. Growth curve modeling showed that infants who gaze followed and looked longer at the target object had significantly faster vocabulary growth than infants with shorter looks, even with maternal education controlled; adding infant pointing strength… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

18
234
1
11

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 324 publications
(268 citation statements)
references
References 22 publications
18
234
1
11
Order By: Relevance
“…In conclusion, the present findings dovetail nicely with laboratory studies of early language learning at the phonetic and word level, showing that an infant's ability to pick up on information in the social context is strongly linked to learning a novel natural language (22)(23)(24)(25). The present study shows that this social information--quality encounters in which interpretation is transparent to socio-visual inspection--is delivered to varying degrees by parents in natural settings, and that its presence predicts later language skills.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…In conclusion, the present findings dovetail nicely with laboratory studies of early language learning at the phonetic and word level, showing that an infant's ability to pick up on information in the social context is strongly linked to learning a novel natural language (22)(23)(24)(25). The present study shows that this social information--quality encounters in which interpretation is transparent to socio-visual inspection--is delivered to varying degrees by parents in natural settings, and that its presence predicts later language skills.…”
Section: Resultssupporting
confidence: 83%
“…However, these potentially informative linguistic cues are largely inaccessible to the rank novices (14-to 18-mo-olds) whose learning environments we study here (21). In contrast, nonverbal cues (e.g., the presence and salience of a word's referent, whether it is being looked at, pointed to, or manipulated by the adult interlocutor) are available from earliest infancy and can, at times, simplify the task of inferring word meaning from situational context (22)(23)(24)(25). Attempts have been made to investigate these nonverbal cues using detailed coding systems (26-28).…”
mentioning
confidence: 99%
“…Those codes are deciphered mostly by the mother or by the person with the mother's role (1) . Other studies (3,4) have shown that the babies with 10 to 11 months that were able to follow the adult's gaze direction and to vocalize spontaneously in a proto-declarative attitude presented earlier vocabulary understanding and gestural production than those that presented just vocalizations. It reinforces the role of the ability to follow the other's gaze to the language acquisition process.…”
Section: Introductionmentioning
confidence: 94%
“…Razvoj besednjaka poteka v obdobju malčka zelo hitro (Brooks in Meltzoff, 2008;Fenson idr., 2004;Marjanovič Umek, Fekonja, Kranjc in Bajc, 2008), pri čemer razumevanje besed v razvoju časovno predhodi rabi leteh (Bates in Goodman, 2001;Fenson idr., 2004;Reynell, 1979). Dojenčki za sporazumevanje z odraslimi najprej rabijo glasove, in sicer jok, vokalizacijo, bebljanje in naključna posnemanja glasov brez razumevanja njihovega pomena (Bates in Goodman, 2001;Siegler, 1998).…”
unclassified
“…Dojenčkove geste pogosto spremlja vokalizacija in neposreden očesni stik z osebo, s katero se sporazumeva (Messinger, Fogel in Dickson, 1999). R. Brooks in Meltzoff (2008) ugotavljata, da sta pogostnost dojenčkovega sledenja s pogledom pogledu odrasle osebe in pogostnost kazanja na predmete med 10. in 11. mesecem starosti pomembna napovednika hitrosti naraščanja obsega malčkovega besednjaka do drugega leta starosti. Malčki z gestami in kazanjem na predmete dodatno pojasnjujejo pomen svojih enobesednih izjav, ko npr.…”
unclassified